URGENSI PENJATUHAN PIDANA MATI TERHADAP PELAKU TINDAK PIDANA NARKOTIKA DAN RELEVANSINYA DALAM PERSPEKTIF Hukum, HAK ASASI MANUSIA DAN HUKUM ISLAM - Laman, Ilham; Agustan; Sabaruddin; Haryanto, Wawan; Harun, Amrullah (IAIN Palopo, 2022)
Indonesia as a country with the largest Muslim majority in the world, recognizes that the death penalty is appropriate and urgent in certain crimes or crimes that affect general problems, threaten human life and state problems. However, if based on the concept of capital punishment and narcotics crime, it can be concluded that it is necessary to study more than the urgency of imposing capital punishment on narcotics criminals. human beings to live and is contrary to the concept of the purpose of resocialization punishment so that the perpetrator can become a better person and can return to society. Through the problem the author then describes with a qualitative method, this method is a problem with social problems based on conditions of reality (real) and natural settings that complex and detailed, qualitatively trying to gain understanding, enlightenment on the phenomenon of research and exploitation in the same situation. because this crime causes passive victims, requires rehabilitation and law enforcement costs, destroys youth, and supports society and the state. In Islamic law, the term Qishash is known, which is an equal punishment for one person's actions against another person, in this case the death row inmates, where the main perpetrator has been executed by the death penalty for drug offenders, it is appropriate because they do damage to every aspect of life. nation and state.